PERUBAHAN SISTEM HUKUM MENUJU JATI DIRI SEBUAH NEGARA - Emy Hajar Abra (UNISSULA, 2016)
Legal system of a state determine the main source of law in making a legal policy, clearly legal systems has certain characteristic although on the development differences among legal system cannot be seen clearly.To comprehend and strengthen the legal systemof a staterequired an observation toward legal system of other states as comparison. The function of legal systems comparison is the basis to grouping states into the family of legal system.Basically legal system describes legal form of a state, hence when a legal system createdfrom structure, substance and culture of certain state the legal system must reflect the state identity. Several factors influence the process to develop a legal system, such as economics, political and social. Means, legal system could be form not only by internal values but also external factorsof state. As a result to avoid legal systems with thin similarities and differences, finding a suitable legal system that in line with the identity of a country is a better way.Discussion about the thin differences between Continental European and Anglo-Saxon do not get big attention as before, impressed ignored and turn out trigger of questions. Why a stateunable to consistently espoused the legal system?, whethergrouping legal systemsinto family of legal system no longer important?. This paper will answer those question by deeply examinethe restorationof legal system so that in line with the historical value of a state. Colonized states often apply legal system that comes from colonizer after independent which means their legal system is notthe state pure legal system that can be incompatible with the values that develop in a state. Would be inconsistent when the legal system applied is Continental European, but in fact the values, laws, institutions and legal verdict are based on the values of religious, Islam for instance.Gambia,a state in Africa with 95% of population is Muslim and the former British colonytake a big step by leave the legacy of colonial legal system, Anglo-Saxon. Gambia. How could a state forced to follow the legal systems of other states remember law is an independent rule, free from interference and coercion. This is the focus study will explain about that when legal system with openness value must have consistency with values that recognizedand upheld by society in a state. As a result changes in a legal system toward identity of a country are necessity and inevitable. On the other hand, debates and critics on the thin differences of legal system should be an independent study to discuss.